Service Innovation: In Highly Competitive of Hotel Industry - Widjaja Hartono (UBL, 2013)
Service innovation is a new or significantly improved service concept that is taken into practice. It can be for example a new customer interaction channel, a distribution system or a technological concept or a combination of them. A service innovation always includes replicable elements that can be identified and systematically reproduced in other cases or environments. The replicable element can be the service outcome or the service process as such or a part of them.(Finland, 2009)Being developed for centuries, Hotel Industry has been in its maturity period for a long time. Confronted with fierce competition and the current global economic crisis, it becomes a hot topic in Hotel Industry how to maintain and raise revenues. By shifting focus from âGoods-Dominant Logicâ to âService-Dominant Logicâ, Service Science presents a new perspective on value creation and service experience. In this new perspective, value is co-created by various roles, experienced and evaluated by customers. However, the problem is how to implement theories in a specific industry.The purposeofthis researchisto discuss the importance of using service innovationin hotel industry in order to win acompetition in this highly competitive industry .